Breast cancer patients’ beliefs, behaviors, and knowledge about the value of physical therapy in their rehabilitation - Kabashi, Doruntina; Hoti, Flaka; Kabashi, Laorent; Terziqi, Hasime; Hoxha, Faton; Goqaj, Lirigzon; Ukëhaxhaj, Antigona (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to examine breast cancer patients’ knowledge, attitudes, and practices regarding physical therapy and its impact on rehabilitation after surgery and radiotherapy. A cross-sectional design was used, involving 67 women who had undergone surgery or radiotherapy for breast cancer. Participants completed a valid and reliable self-prepared questionnaire comprising of 32 questions. The data were analyzed using IBM SPSS version 25. Results showed that 46.2% of patients were unaware of the role of physical therapy in breast cancer rehabilitation. Patients with higher education and those over 60 years old, demonstrated significantly greater knowledge about physical therapy (p < 0.05). Access to physical therapy services was limited, with only 14.9% receiving it post-diagnosis and 20.9% post-surgery. For those who received physical therapy sessions after surgery, positive correlations were found between physical therapy and improvements in mobility (r = 0.355, p ≤ 0.05) as well as pain and muscle tension relief (r = 0.602, p ≤ 0.05), and result for the variable pain (r = .202*, p ≤ 0.05). These findings underscore the need for increased awareness about physical therapy, improved access to services, and better communication from healthcare providers to optimize rehabilitation outcomes for breast cancer patients in Kosovo.